Psicólogo-professor: conhecendo a inserção dos psicólogos na docência do Ensino Superior em Psicologia no Maranhão - MELO, Juliana Salgueiro (2016)
This research aims to analyze the trajectory of insertion of psychologists, graduates in Maranhão, in the teaching of Higher Education in Psychology. It will be such an analysis from the narratives of the professionals in question, including reflections on teaching practice and training of these route. It describes the process of institutionalization of training in Maranhão Psychology 2016 questioning the scene of the teaching of Higher Education in Psychology in Brazil and its implications for training and professional performance. It presents also a mapping of teachers who make up such courses. The survey has a time frame of two years (2014-2016), including in its universe of research higher education institutions that offer graduation in Psychology classes that have already been completed. In this context, we have the Federal University of Maranhão - UFMA, CEUMA University and College Pythagoras, all in the state capital. The theoretical framework is based on the Historiography of references of Psychology and Phenomenology for document analysis and interviews, respectively. For analysis of the bibliographic and documentary material, including legislation and educational policy proposals of the courses, the historical dimension is used, designing teaching practice in this joint process with the past. This information will support to understand the narratives of the participants, psychologists, teachers, research through semi-structured face interviews analyzed from the phenomenological approach. It is considered this work extremely important, since there are no studies focused on this theme illustrating the local reality and professor of psychology, who besides being a psychologist, participates in the process of training other professionals.